Effects of various local analgesics and ketamine for cranial epidural analgesia in Black Bengal Goats - Roy, Animesh; Islam, Md; Hossain, Mohammed; Lucky, Nasrin; Akanda, Md Rashedunnabi; Paul, Bashudeb; Hasan, Mir; Mahfuz, Md; Uddin, Fokor; Roy, Sipra (International Journal of Biological Research, 2014)
The present study was conducted to find out the effects of analgesic and anaesthetic drugs for cranial epidural analgesia in Black Bengal goats. A series of thirty two (n=32) analgesic trails were conducted in goats age ranged from 8 to 12 months and with an average body weight of 8.1 kg. The animals were divided into four groups (n=4) and a replication of 8 trails was performed in each group at least one week interval. Two percent (2%) lidocaine hydrochloride (6.0 mg/kg), 2% lidocaine hydrochloride with adrenaline (6.0 mg/kg), 0.5% bupivacaine hydrochloride (1.5 mg/kg) and ketamine hydrochloride (5.0 mg/kg) were used to perform cranial epidural analgesia. 2% Lidocaine hydrochloride and Ketamine hydrochloride showed rapid onset of analgesia. 0.5% bupivacaine hydrochloride produced the highest area of desensitization in thigh region during cranial epidural analgesia. Perineal region and tail were totally desensitized during epidural analgesia. 0.5% bupivacaine hydrochloride prolonged the duration of analgesia during epidural analgesia. 2% Lidocaine hydrochloride showed no side effects whereas 2% Lidocaine hydrochloride with adrenaline showed straining and muscle tremor, 0.5% bupivacaine hydrochloride shivering and drowsiness, ketamine hydrochloride tympany, excitement and drowsiness. It seemed that 2% Lidocaine hydrochloride is more effective whereas 0.5% bupivacaine hydrochloride is associated with side effects. Though ketamine hydrochloride is a dissociative agent, it could also be used in epidural analgesia.